The distinction between charisma and vision. - Lee, Tracy Hway. (2008)
There appears to be a particular trend in research on chrismatic leadership. Most of it subsumes vision within charisma. Some scholars even suggest that it is the vision that leads to the attribution of charisma to the leaders in the first place. However, we think that charisma and vision are two distinct concepts and as such a leader may be charismatic and visionary, or neither. To us, charisma is an emotion-based construct or a "heart" thing and charismatic leaders understand their social environment very well and are masters of social skills.